การวิเคราะห์ความไม่แน่นอนในแบบจำลองพลวัตและการออกแบบตัวควบคุมคงทนสำหรับการควบคุมกำลังการผลิตและความถี่ - จีรนุช จึงอุดมพร (จุฬาลงกรณ์มหาวิทยาลัย, 2004)
The load frequency control (LFC) aims to sufficiently generate electricity to meet users’ demand and to maintain frequency in a standard range. However, the characteristic of power consumption is changing over time which leads to a large variation of working operation in power generation processes. This variation deteriorates the performance of power generation and sometimes causes instability. This thesis presents impact analysis of changing power consumption or working operation to dynamic models as well as describes the dynamic difference by means of bounded real parametric uncertainties. The study indicates that the state-space models consist of two uncertain parameters, namely, turbine time constant and synchronizing torque coefficient. In addition to the uncertainty analysis, the thesis presents robust H2 controller synthesis for LFC system subject real parametric uncertainty. The design approach employs the robust synthesis technique previously developed for Lur’e systems which consider each uncertainty as a nonlinear function satisfying sector condition. Numerical examples demonstrate an application of uncertainty analysis to the robust control design subject to changes in electrical power consumption. In particular, the designed controllers can guarantee stability and performance of LFC system under bounded uncertainty.